(untitled) (AYUSHDHARA, 2020)
PCOS is mainly characterised with abnormalities in the metabolism of androgens and estrogen and control of androgen production and can result from abnormal function of the hypothalamic-pituitary-ovarian axis. The incidence of PCOS in adolescent and reproductive age women is increasing alarmingly due to westernized culture, faulty dietary habits & lifestyle, rapid urbanization, excessive work load etc. In Ayurveda literature no as such direct correlation of PCOS with any disease is found, though symptomatically menstrual abnormalities amenorrhea or delayed cycle etc. can be correlated with Lakshana and Samprapti of Nashtartava, Artavakshaya. According to Acharya Sushruta in Nashtartava, artava is obstructed by vitiated Doshas and in Artavakshaya menstruation is delayed, menstrual blood is scanty and associated with pain in Vagina. Mainly Dushti of Rasadi Dhatu occurs, resulting in improper formation of Upadhatu i.e., Artava. The features of PCOS may also be correlated with Pushpaghni Jataharini that is described in Ayurvedic classics (Kashyapa Samhita) having the clinical features of futile ovulation (Vrutha Pushpa) and corpulent hairy cheek (Sthula Lomashaganda). In this Article an attempt is made to understand the specific Artava Nasha feature in relation to Nashtartava Samprapti and to find approach for the treatment from the basal level. Conclusive treatment modalities obtained are i.e., Nidanaparivarjana, Sanshodhana, Agneya Dravya uses in PCOS.